Pengaruh PAD dan Dana Perimbangan Terhadap Pertumbuhan Ekonomi Pada Kawasan Gerbangkertosusila Tahun 2017 - 2021 - Yulianto, Irfan Tri; Akbar, Fajar Syaiful (STAI Denpasar Bali, 2024)
The study aimed to examine how Local Own-Source Revenue and Balancing Funds influenced the Economic Growth of Regency/City Governments in the Gerbangkertosusila Area between 2017 and 2021. Employing a quantitative approach via Saturated Sampling, the research utilized GRDP data from the East Java Province BPS website to evaluate Economic Growth, and the Statement of Budget Realization data from the official websites of the Regency/City Governments in the Gerbangkertosusila Area. Multiple linear analysis was employed for data analysis. The findings indicated a positive correlation between Local Own-Source Revenue and Economic Growth in the Gerbangkertosusila Area, while the Balancing Fund did not exhibit a significant impact on the region's economic growth.